Możliwości absorpcji przez Polskę funduszy strukturalnych w pierwszych latach członkostwa w Unii Europejskiej - Więznowska, Katarzyna (The potential of structural funds absorption in the first years of EU membership, 2006)
The Poland’s EU membership and our right to use structural funds create a chance of economic and social activation. But the scale of benefits depends on effectiveness of funds absorption by final users of funds. One should be aware of the fact that part of funds cannot be the used without proper preparation of administrative structures and achieving sufficient absorption abilities. The article presents the goals and rules of using the EU aid resources for decreasing regional inequality. The level of structural help for member countries between 2000 and 2006 is compared and described. In the last part the absorption potential and scale of structural funds use in Poland 2004 are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 248-265